Women's social networks and use of facility delivery services for uncomplicated births in North West Ethiopia: a community-based case-control study - Kerebih Asrese; Margaret E. Adamek (BMC, 2017)
Abstract Background High maternal mortality has remained an unmet public health challenge in the developing world. Maternal mortality in Ethiopia is among the highest in the world. Since most maternal deaths occur during labor, delivery, and the immediate postpartum period, facility delivery with skilled birth attendants is recommended to reduce maternal mortality. Nonetheless, the majority of women in Ethiopia give birth at home. Individual attributes and availability and accessibility of services deter service utilization. The role of social networks that may facilitate or constrain service use is not well studied. Methods Community-based case-control study was conducted between February and March 2014 in Jabi Tehinan District, North West Ethiopia. Retrospective data were collected from 134 women who had uncomplicated births at health facilities and 140 women who had uncomplicated births at home within a year preceding the survey. Interviews were held with eight women who had uncomplicated births at health facilities and 11 who had uncomplicated births at home. The quantitative data were entered and analyzed using SPSS for Windows versions 16.0 and hierarchical logistic regression model was used for analysis. The qualitative data were transcribed verbatim and data were used to substantiate the quantitative data. Results The results indicated that social network variables were significantly associated with the use of health facilities for delivery. Taking social networks into account improved the explanation of facility use for delivery services over women's individual attributes. Women embedded within homogeneous network members (Adjusted OR 2.53; 95% CI: 1.26-5.06) and embedded within high SBA endorsement networks (Adjusted OR 7.97; 95% CI: 4.07-12.16) were more likely to deliver at health facilities than their counterparts. Women living in urban areas (Adjusted OR 3.32; 95% CI: 1.37-8.05) and had better knowledge of obstetric complications (Adjusted OR 3.01; 95% CI: 1.46-6.18) were more likely to deliver at health facilities. Conclusion Social networks facilitate SBA utilization by serving as a reference for the behavior to deliver at health facilities. These findings inform health professionals and other stakeholders regarding the importance of considering women's social networks in designing intervention to increase the proportion of women who deliver at health facilities.